2021
DOI: 10.15173/ijsap.v5i2.4397
|View full text |Cite
|
Sign up to set email alerts
|

Improving the student learning experience through the student-led implementation of interactive features in an online open-access textbook

Abstract: This case study highlights the work of Students as Partners (SaP) as a balanced approach for implementing and evaluating an online open-access textbook in introductory animal physiology at the University of Toronto Mississauga. Started in 2017 with an eCampus Ontario grant, the project involved undergraduate and graduate students developing and improving an open-access e-textbook to support student learning in a second-year undergraduate introductory animal physiology course. This case study focuses on the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Accessibility, portability, and convenience are additional benefits mentioned in previous etextbook studies (Ambra et al, 2022;Tarmizi & Al-odeh, 2021). In this study, students indicated that the most beneficial aspects of the learning process were finding a topic, marking pages, tutorial videos, and quizzes with immediate feedback (Sharma et al, 2021;Wu & Chang, 2021). On the other hand, two students (5%) were concerned about the Internet network, and two others (5%) experienced discomfort when reading on their mobile devices.…”
Section: Developmentioning
confidence: 75%
“…Accessibility, portability, and convenience are additional benefits mentioned in previous etextbook studies (Ambra et al, 2022;Tarmizi & Al-odeh, 2021). In this study, students indicated that the most beneficial aspects of the learning process were finding a topic, marking pages, tutorial videos, and quizzes with immediate feedback (Sharma et al, 2021;Wu & Chang, 2021). On the other hand, two students (5%) were concerned about the Internet network, and two others (5%) experienced discomfort when reading on their mobile devices.…”
Section: Developmentioning
confidence: 75%
“…The results of this study indicate that the adoption of an affordable and practical learning model can stimulate interest in learning, facilitate independent learning, and increase students' confidence in their ability to learn. Moreover, integrating mobile technology into PjBL can contribute to implementing paperless programs [44], and enhance student engagement in online learning environments through interactive quizzes, video tutorials, and collaborative project assignments [45].…”
Section: Discussionmentioning
confidence: 99%
“…The use of information technology in education has been widely carried out by various universities throughout Indonesia in the world (Nugroho, et al, 2020). A study said that ICTsupported learning such as discussion forums and short videos discussing material contribute to constructivism and observational learning aspects (Sharma, et al, 2021). One of the mathematics materials taught in class VII odd semesters is Linear Equations of One Variable.…”
Section: Introductionmentioning
confidence: 99%